Maple Syrup Urine Disease in a Central Indiana Hereford Herd - Mark E. Robarge; Jonathan E. Beever; Stephen D. Lenz; Christopher J. Lynch; William L. Wigle (Case Reports in Veterinary Medicine)
Maple syrup urine disease (MSUD) and further cases were identified in herd mates of a small Hereford herd in Indiana based on history, clinical signs, microscopic lesions, and biochemical and genetic testing. This aminoacidopathy has been diagnosed in polled Shorthorn, polled Hereford, and Hereford cattle in Australia, Uruguay, Argentina, and Canada and is the result of a mutation of the branched-chain alpha-ketoacid dehydrogenase complex. The Indiana index calf case was confirmed by showing the classic accumulation of ketoacids in liver that results from a defect in the E1-alpha subunit (248 C/T haplotype) in the mitochondrial branched-chain α-ketoacid dehydrogenase complex. The presence of the mutation was confirmed in the index case, the dam, and four related herd mates that represent the first confirmed cases of bovine MSUD mutation in United States cattle.